Aplikasi Penerjemahan Aceh-Indonesia Berbasis Android - Pratama, Angga; Ilhadi, Veri; Muharram, Rachmad (Jurnal Tika, 2023)
The Aceh-Indonesian dictionary can be used as a starting point for learning the Acehnese language. A dictionary is usually synonymous with a book, which sometimes presents difficulties when carrying it anywhere. Now, as technology develops, dictionaries can be made via an Android application, which makes it easy for users to bring dictionaries anywhere. This Aceh-Indonesian Dictionary application was created using the Java programming language and SQlite as a database storage medium based on the results of the average value acquired. The Likert Scale Questionnaire stated that 63% of users agreed that the Aceh-Indonesian Dictionary application was useful for learning Acehnese vocabulary. -Indonesia